Penanganan Kredit Bermasalah (Non Performing Loan) Pada PT. BPR BKK Muntilan (Perseroda) - Risma Usriyati; Nuwun Priyono; Nibras Anny Khabibah (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
This study aims to determine the factors that cause non performing loans, and to find out how to deal with non performing loans at PT. BPR BKK Muntilan (Perseroda) Operational Head Office. The method used in this study is a qualitative data analysis method, in this method a process is carried out to systematically track and organize field notes that have been obtained from observations, interviews, literature studies, and documentation so that research can report research results. The emergence of non performing loans at PT.BPR BKK Muntilan (Perseroda) Operational Head Office due internal and external factors of banks and debtors, namely the analysis officer is not careful when analyzing debtors, decreased debtor sales turnover, and because of the pandemic. The results of the study stated that efforts to handle non performing loans were carried out by restructuring, namely by changing credit terms involving all or part of arrears by rescheduling and making re-conditions